Dominant Role of Sea Level on the Sedimentary Environmental Evolution in the Bohai and Yellow Seas Over the Last 1 Million Years - Shi, Xuefa; Yao, Zhengquan; Liu, Jianxing; Qiao, Shuqing; Liu, Yanguang; Li, Xiaoyan; Fang, Xisheng; Li, Chaoxin (Frontiers in Earth Science, 2021)
Transgression and regression deposits from the shallow continental margin provide information on orbital-scale variations in sea level, climate change, and local tectonics. In this study, we conduct a high-resolution chronological and sedimentological analysis of a 125-m core (NHH01) drilled in the southern Yellow Sea. We developed a high-resolution age model at the orbital timescale over the last ~1 Myr by the astronomical tuning of the sediment grain size. Sedimentological analysis and environmental proxies reveal that the study area is characterized by cyclic alternations of neritic and littoral/fluvial deposits controlled by glacial–interglacial sea-level changes. These results confirm the earlier assumption that sea-level fluctuations play a dominant role in the sedimentary architecture of the southern Yellow Sea. Moreover, only low-frequency sea-level fluctuations (~100 kyr) were preserved in the NHH01 sequence; however, additional high-frequency (~40 kyr) sea-level variations were also present in the sediments of the shallower Bohai Sea. Despite the large spatial difference, this finding implies that the sedimentary environment in the eastern marginal seas of China had been influenced by the sea level as a whole over the last 1 Myr. The comparison of the sedimentary environment with other cores from the Bohai Sea, Yellow Sea, and coastal region, as well as records from Indonesia and Japan, reveals that a consistent initiation of large-scale marine transgression occurred at ~0.8–1 Ma. This phenomenon was likely caused by the long duration of glacio-eustatic high sea-level stands following the Middle Pleistocene transition, which is characterized by a shift in glacial cycles from 40 kyr to 100 kyr.